Stable multiwavelength erbium-doped random fiber laser - Saleh, Suhairie (2019)
Multiwavelength fiber lasers which consist of equally-spaced frequency components have found many applications and that includes as light sources for optical communication systems. One of the techniques available to generate such multiple wavelengths is random fiber lasers. Despite simplicity in structure due to the avoidance of mirrors in random fiber lasers, the number of comb lines generated is rather limited with only four comb lines are generated within 3 dB flatness at the 60 mW pump power. In optical communication systems, such a limitation in the comb lines could be a hindrance for the attainment of high-speed data communication due to the lack of light sources. Aspired to solve the problems and bring random multiwavelength to new heights, performances of multiwavelength random fiber lasers are improved in this thesis work. Based on the random Rayleigh scattered feedback of a 25 km long single-mode optical fiber, multiwavelength lasers are successfully generated. The linear cavity in which one end is formed by a mirror and the other end by the random Rayleigh scattered feedback is able to generate 27 laser lines within 3 dB flatness at the pump power of 350 mW. In addition, the laser lines generated are also stable with power fluctuations less than 0.6 dB over an hour duration. All in all, the study in this work is found to be effective in elevating the performances of multiwavelength random fiber lasers to further heights.